THE EFFECT OF ACCEPTANCE AND COMMITMENT THERAPY (ACT) ON ANXIETY LEVELS IN ELDERLY LIVING AT PANTI SOSIAL TRESNA WERDHA (PSTW) BALI - Wicaksana, I Gusti Agung Tresna; Wahju S, Teguh; Eko K, Rinik; Yudara S, Putu (Public Health of Indonesia, 2018)
Background: Panti werdha in Indonesia is considered as a nursing home for elderly. However, there are still psychosocial problems occur such as loneliness, sadness, and anxiety disorders. Acceptance and Commitment Therapy (ACT) may be able to solve psychosocial problems especially for anxiety.Objective: To analyze the extent of ACT's influence on the level of anxiety of the elderly living in the PSTW Bali.Methods: This study was a quasi-experimental study with pretest posttest with control group. Sixty elderly were recruited and divided into control and treatment groups with 30 samples of each group. Paired and Independent T-test were used for data analysis.Results: The paired T-test results in the control group showed significant differences of anxiety score between pretest and posttest after given generalist therapy (p <0.05). The result of paired T-test in the treatment group showed that there was a significant difference of anxiety score between pretest and posttest after given general and ACT therapy (p <0.05). The independent T-test showed that there was a significant difference of anxiety score between control group and treatment group (p <0.05).Conclusion: ACT psychotherapy is effective in decreasing anxiety in elderly who are living in PSTW Bali.